A study of collection development practices of the children's library - Umandap, Mary Anne L. (Institute of Library Science, University of the Philippines Diliman, 2002)
Childhood is very short and it is important that the child should be exposed to all forms of literature suitable to his/her stages of development. Nowadays, children are deprived of normal contact through play and participation with other people. It is vital therefore for them to develop their full potential, because childhood should be rich both educationally and socially.